PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN LQ45 PERIODE 2013-2017 - Ikhsan, Nuri Maulana; Dermawan, Yohanes Rully (Manajemen & Bisnis Jurnal, 2019)
This study aims to determine the effect of financial ratios on stock prices. Financial ratios used in this study is the Current Ratio, Debt to Equity Ratio, Return On Equity, Total Asset Turnover, Earning Per Share, and Price to Book Value. The type of research used is quantitative to observe the effect of financial ratios on stock prices. This study used a purposive sampling method with a total sample of 20 companies registered in the LQ45 index for the period 2013-2017 and fulfilling the research criteria. The statistical method used is multiple linear regression analysis The results of this study indicate that partially, the variable debt to equity ratio, return on equity, total asset turnover, earnings per share, and price to book value have a significant partial effect on stock prices, while the current ratio variable does not have a partial significant effect on stock prices. Simultaneously the current ratio variable, debt to equity ratio, return on equity, total asset turnover, earnings per share, and price to book value have a significant simultaneous effect on stock prices. And the most dominant influential variable is earnings per share. Keywords: Current Ratio, Debt to Equity Ratio, Return On Equity, Total Asset Turnover, Earning Per Share, Price to Book Value, and Stock Price.